2018
DOI: 10.1124/dmd.118.081737
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of 21 Allelic Variants of Dihydropyrimidine Dehydrogenase Identified in 1070 Japanese Individuals

Abstract: to wild-type DPD. Moreover, the band patterns observed in the immunoblots of blue native gels indicated that DPD dimerization is required for enzymatic activity in DPD.Thus, the detection of rare DPYD variants might facilitate severe adverse effect prediction of 5-FU-based chemotherapy in the Japanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 28 publications
(32 reference statements)
2
40
0
Order By: Relevance
“…A recent study has reported the functional characterization of 21 allelic variants of DPYD identified in 1070 Japanese individuals 14 . Five of the variants (p.Val335Met, p.IIe543Val, p.Val732IIe, p.Thr768Lys, p.Asn893Ser) identified in our present analysis were among those described in that earlier study.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…A recent study has reported the functional characterization of 21 allelic variants of DPYD identified in 1070 Japanese individuals 14 . Five of the variants (p.Val335Met, p.IIe543Val, p.Val732IIe, p.Thr768Lys, p.Asn893Ser) identified in our present analysis were among those described in that earlier study.…”
Section: Discussionsupporting
confidence: 70%
“…More than 450 DPYD variants have been identified to date as a cause of 5FU‐related toxicity in patients with cancer 14 . In the context of 5FU, 4 DPYD variants identified in the White population are known to have an impact on enzyme function and FP‐related toxicity risk 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the IRUD project (Japan's Initiative on Rare and Undiagnosed Diseases 9 ) used the reference panel to reduce the discovery of false positive single nucleotide variants (SNVs) during the exome analyses of undiagnosed patients. In another project, CYP SNVs included in the reference panels were selected and analyzed systematically for their effect on drug metabolism [10][11][12] . As seen from these examples, the previous versions of the reference panels worked well; however, there are some limitations.…”
Section: Background and Summarymentioning
confidence: 99%